Analisis Teori Paritas Daya Beli Bahan Pokok: (Studi Kasus pada Pengaruh Dampak Nilai Tukar, Kebijakan Moneter, dan Inflasi di Indonesia) - Gugun, Gugun; Azkiya, Fina Berliana; Putri, Nadya Ananda; Putri, Nandini; Nabilah, Azzah; Syahwildan, Muhammad (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Purchasing power parity (PPP) theory states that the exchange rate between two currencies should reflect the comparative prices of goods and services in both countries, and this study focuses on the effect of exchange rate, monetary policy, and inflation. In this study, secondary data is used to see how domestic and foreign inflation correlates with the Rupiah exchange rate. The results of the analysis show that there is a significant correlation between inflation and the exchange rate, which suggests that appropriate monetary policy is needed to maintain exchange rate stability and people's purchasing power. It is hoped that this research will help policymakers make plans to tackle inflation and increase people's purchasing power. Keywords: Purchasing Power Parity, Exchange Rate, Monetary Policy, Inflation